Eksistensi Pidana Mati Dalam KUHP Baru; Orientasi Dan Implikasi - Candrawati, Dewi Sekar; Mukhlashi, Dhiya; Isfahani, Muhammad Ragib; Rahman, Muhammad Rizal; Huda, Syihaabul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The Criminal Code as a legal rule that has existed since colonial times contains articles related to criminal acts. From several criminal acts that arise, there will also be criminal punishment that must be enforced, one of them is the death penalty. Since the old Criminalogy Code until the new Criminalogy Code was validated, death penalty has always been a topic of discussion and even debate by any Indonesian society through various media, both in cyberspace and in the real world. Death penalty has always been an interesting topic to look at in various aspects of politics, humanity, academics, and even religion. The existence of the death penalty in Indonesia certainly can’t be separated from the pros opinions and cons opinions, considering the impact arising from the enforcement penalty. Especially, since there are differences in classification and provisions for death penalty in the old Criminalogy Code and the new Criminalogy Code. Human rights (HAM) violation such as the right to live and enjoy life is one of reasons of death penalty is not accepted as a punishment for crime.